Strategi Listening Untuk Meningkatkan Keterlibatan Audiens Dalam Public Speaking Formal - Hasanah, Rizka Rohmatul (Jurnal Selasar KPI : Referensi Media Komunikasi dan Dakwah, 2025)
Formal public speaking is not only dependent on good speaking skills but also on effective listening strategies and building empathy with the audience. An effective listening strategy enables speakers to understand audience responses, adjust message delivery, and create more interactive communication. Meanwhile, empathy helps strengthen the connection between speakers and audiences by understanding their backgrounds, needs, and expectations. By combining these two strategies, speakers can enhance audience engagement, clarify delivered messages, and establish a more conducive environment for effective communication. This study employs a qualitative method with a literat ure review approach to analyze the role of listening strategies and empathy in formal public speaking. The findings indicate that listening skills and empathy are key elements in creating more engaging, interactive, and impactful communication.